The distribution of mosquitoes in Romania (Diptera: Culicidae). Part HI: Detailed maps for Anopheles, Aedes and Culex. Issue 14 (2003) - Nicolescu, Gabriela; Vladimirescu, Alexandru; Ciolpan, Octavian
No abstract available